On Chung-Teicher Type Strong Law of Large Numbers for 𝜌∗-Mixing Random Variables - Anna Kuczmaszewska (Discrete Dynamics in Nature and Society)
In this paper the classical strong laws of large number of Kolmogorov, Chung, and Teicher for independent random variables were generalized on the case of 𝜌∗-mixing sequence. The main result was applied to obtain a Marcinkiewicz SLLN.